Marqueurs discursifs du dire (français, russe, norvégien) - Elizaveta Khachaturyan (Corela)
The communicative activity is based on the adjustment between two speakers because the relationship between words and things is not immediate and obligatory (Culioli). In what is said there is always the indicible (‘impossible to say’) that we don’t manage to express, and the words seem to be insufficient. The speaker tries to reformulate, to explain or to say in a different way, and the discourse markers ‘du dire’ (of the verb ‘say’) are often used in this case to show that what is said does not belong to the speaker (Paillard). The semantics of these discourse markers in French and Russian (i.e., disons and skažem) can be explained through the semantics of the verbs dire and skazat’. But what happens in Norwegian, where the expressions with the verb å si are not very frequent? We will analyze the expressions with the verbs å kale / å hete (‘to call’) that are focused on similar problems.